Achieving high comprehensive energy storage properties of BNT-based ceramics via multiscale regulation. Issue 12 (15th June 2023) - Zhou, Qiyuan; Peng, Zhanhui; Zhang, Fudong; Chai, Qizhen; Wu, Di; Liang, Pengfei; Wei, Lingling; Chao, Xiaolian; Yang, Zupei
Abstract: It is difficult to obtain high polarization strength and high breakdown strength synchronously, resulting in the drawback of lower energy storage density, which inhibits commercial application of energy storage materials. We have successfully prepared (1- x )(0.93Bi0.5 Na0.5 TiO3 -0.07CaSnO3 )- x SrTiO3 (BNT–CS– x ST) ceramics by solid-state method. The presence of polymorphic nanodomains and the large electric displacement generated by the high charge Sr 2+ -Sr 2+ ion pairs help to delay saturation polarization ( P m ∼ 48.64 μC/cm 2 at 315 kV/cm). In addition, the breakdown field strength ( E b ) is increased by grain refinement and increasing the band gap. It is noteworthy that a high recoverable energy storage density ( W rec = 4.2 J/cm 3 ) and a great efficiency ( η = 88%) were achieved simultaneously in BNT–CS–0.5ST ceramic. Moreover, excellent charge-discharge performance was also achieved, with a discharge energy density W d of 2.2 J/cm 3, a current density C D of 1724 A/cm 2 and a power density P D of 250 MW/cm 3 . The study demonstrates that the great potential of BNT–CS– x ST ceramics in power storage devices and provides an effective strategy for designing ceramics dielectric capacitors with excellent performance.